Morphophysiological Response of Rice Genotypes to Seed Priming in Various Environments - Akmal; Annas Boceng; Suryanto; Asrijal; Sukriming Sapareng; Taruna Shafa Arzam AR; Rahmi Azizah Mudaffar; Rosnina; Sumantri (Postgraduate, University of Mataram, 2025)
Seed priming with PEG 6000 is a pre-planting technology that has the potential to increase rice tolerance to drought stress and improve plant establishment in various seedling systems. This study aimed to examine the morphophysiological responses of three rice genotypes (IR64, Ciherang, and Cakrabuana) to seed priming with PEG 6000 at various concentrations and in different seedling systems. The study was conducted in two stages: (1) testing the tolerance of genotypes to drought stress using PEG 6000 concentrations of 0, 50, 100, and 150 g L⁻¹ at the germination stage, and (2) evaluating the effectiveness of priming at the vegetative stage with wet and dry seeding systems. A concentration of PEG 6000 at 100 g L⁻¹ provided optimal priming effects with a 15-25% increase in germination percentage and a 20-35% increase in seedling vigor compared to the control. The Cakrabuana genotype showed the best tolerance to drought stress, followed by Ciherang and IR64. Seed priming with PEG 6000 at a concentration of 100 g L⁻¹ effectively enhanced the drought tolerance and adaptation of rice genotypes in various germination systems, with varying responses among genotypes.